Greeks and Victorians: A Re-Examination of Engels’ Theory of the Athenian Polis - Lee, Richard B. (Culture)

(untitled) (Canadian Anthropology Society / Société Canadienne d’Anthropologie (CASCA), formerly/anciennement Canadian Ethnology Society / Société Canadienne d’Ethnologie, 1985)
There is a paradox in Engels’ well-known theory of state formation contained in The Origin of the Family Private Property and the State. The state in Engels’ view represented a triumph of a small elite of non-producers over the vast majority, and a world-historical defeat for the common people. Yet the Athenian state, Engels’ prime example, does not conform to the pattern: it becomes more “democratic” as the state evolves rather than less. The paper explores the way out of this dilemma, through an examination of the rise of the Athenian polis in light of the recent theory of the Early State put forward by Henri Claessen and Peter Skalnik. The analysis offers insight into the internal dynamic of early states and the role of kinship, and in the final section argues for the essential validity of Engels’ view.